Two new species of the genus Vekunta Distant (Hemiptera: Fulgoromorpha: Derbidae) from Korea - Rahman, Mohammad Atikur; Kwon, Yong Jung; Suh, Sang Jae (Zootaxa, 2012)
Two new derbid species of the genus Vekunta Distant, V. fuscolineata sp. nov. and V. jahini sp. nov. (Hemiptera: Fulgoro-morpha: Derbidae: Cenchreini), are described and illustrated from Korea. They represent the first record of the genus Vekunta Distant, 1906 in the Korean fauna. A checklist of species and a key to the known species of the genus are provided.